REFLEKSI TENTANG KONSEP KEBUDAYAAN: SEBUAH CATATAN AUTOETNOGRAFI - Novianti, Kurnia (P2KK LIPI, 2013)
This paper is a reflection of a concept that becomes a central concern in the study of anthropology, namely culture. The concept of culture is interesting to be debated because the author assumes that the meaning of culture is rich and highly dependent on the paradigm of the person or group of people, who interpret it. By using the memory of life experiences and supported by every day observation as the data, the author aims to understand what culture is. Nevertheless, the life trajectories that are still being experienced today still leave the question about the culture itself. Keywords: life experience, reflection, culture, autoethnography